The Relationship between Personal Mastery and Teachers’ Competencies at Schools in Indonesia - Settaraming Algi; Mohd Anuar Abdul Rahman (Intelektual Pustaka Media Utama, 2014)
The purpose of the present research is to study the relationships between indicators of personal mastery and indicators of teachers’ competencies at Junior Secondary State Bone district in Indonesia. The respondents of the research consists of all the Junior Secondary State teachers of the Bone district including 200 teachers (80 males 120 females). The obtained data was analyzed by Structural Equation Modeling (SEM). The results have indicated that there exists a significant correlation between personal mastery and teachers’ competencies at the 0.05 significance level. Further, a significant positive correlation was observed between the indicators of personal mastery (personal vision, creative tension, commitment, trust, and consciousness) and indicators of teachers’ competencies (pedagogic, professional, personality, and social).